Structural design and analysis of a microturbine compressor - Maharsi, Indra Wening (2006)
A structural design was conducted on a compressor for a microturbine generating 100 kW output power. The scope concerned the conceptual design of gas turbine system, the sizing of the compressor, the computation of loads acting on compressor and the stress analysis for its structural integrity. The dimensions and the physical properties of the compressor impeller were calculated based on the given microturbine output power, using thermodynamic equations on turbomachinery aspects. Thereafter a simplified one-tenth model of the ten-bladed impeller was created in Fluent, a Computational Fluid Dynamic (CFD) program, taking into consideration the axisymmetric boundary conditions. The analysis was run at the standard sea level atmospheric conditions (ISA) to obtain the fluid forces acting on the blade surfaces. These forces, together with the rotational inertial loads, were then used as the loading input parameters for the structural integrity analysis done using the Finite Element program MSC.Nastran. The resulting stresses and deformations were obtained and contours plotted. Comparisons were done between the curved blade and the straight blade designs. The results showed that the curved blade gave better stress distribution, thus this shape was then tested for various rotational speeds. Analyses were also conducted on different materials for the compressor impeller structure, and steel was subsequently demonstrated to be the one which was to be suitable and safe.